Frequency and Stochastic Domain Models for Two Geometries of the IPS Wave Power Buoy - Cândido, J. (2011)
Frequency-domain analysis is applied to a geometry of the original IPS buoy device concept. The analysis is particularly useful in the early development stages to establish the response of power take-off mechanism characteristic parameters to different frequencies of the wave spectrum. Optimal mechanical damping and spring coefficients are computed for some parameters restrictions. Absorbed power, capture width and other variables, such as relative displacement,are computed for regular waves and these optimal mechanical coefficients. A stochastic model is developed in order to evaluate the IPS buoy behaviour for irregular waves’ conditions. This allows defining probability density functions for parameters that characterize the device’s behaviour. Assuming that the overall system behaviour is linear and that the surface elevation for irregular waves may be regarded as a stochastic process with a Gaussian probability density function, the variables that define the system behaviour, such as bodies’ displacements and velocities, will also hold a Gaussian probability density function. The average power extraction is computed for different sea state conditions.Aiming to enhance the device’s hydrodynamic performance, a new non-axisymmetric IPS geometry is conceived. Using the stochastic modelling approach, the device’s behaviour is studied for several wave directions and compared to the axisymmetric configuration’s behaviour.